Derivational and Semantic Features of Complex Syntactic Constructions: Theoretical Foundations and Analytical Approaches - Xamrayeva, Zebiniso (The Lingua Spectrum, 2025)
This article examines the nature of complex syntactic constructions, the interrelation between syntactic and semantic factors in their formation, and analyzes the main theoretical approaches in modern linguistics. The study examines various types of complex sentences – compound, complex, mixed, period, and prosaic stanza – considered as forms of complex syntactic constructions. Special attention is given to the interrelationship between language and speech, focusing on their structural, derivational, and communicative properties. The scientific views of Ch. Hockett, N. Chomsky, O. Jespersen, G. Paul, and J. Antoine are analyzed, highlighting both the shared and divergent aspects of their theories concerning syntactic derivation and deep structure. G. Paul’s idea that “in two-component complex sentences, one component explains the other” is illustrated with examples and interpreted as an important feature revealing the semantic essence of complex syntactic constructions. The article also compares the perspectives of Turkish and Russian linguists, emphasizing that the issues of text syntax have not yet been fully resolved. In conclusion, the interconnection between speech and text in the analysis of complex syntactic constructions is scientifically substantiated, and the status of the text as a syntactic unit larger than the sentence is justified.